2020
DOI: 10.1109/access.2020.3026037
|View full text |Cite
|
Sign up to set email alerts
|

Corticomuscular Co-Activation Based Hybrid Brain-Computer Interface for Motor Recovery Monitoring

Abstract: The effect of corticomuscular coactivation based hybrid brain-computer interface (h-BCI) on post-stroke neurorehabilitation has not been explored yet. A major challenge in this area is to find an appropriate corticomuscular feature which can not only drive an h-BCI but also serve as a biomarker for motor recovery monitoring. Our previous study established the feasibility of a new method of measuring corticomuscular co-activation called correlation of band-limited power time-courses (CBPT) of EEG and EMG signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…Only four studies targeted the lower limbs [ 26 , 61 , 70 , 77 ], all focused on ankle dorsiflexion. The upper limb motor tasks included shoulder ab/adduction (n = 1) [ 63 ], reaching (n = 5) [ 59 , 60 , 65 , 68 , 74 ], grasping (n = 5) [ 4 , 41 , 64 , 66 , 67 ], reaching and grasping (n = 2) [ 71 , 73 ], hand and wrist extension (n = 2) [ 22 , 23 ], and finger extension (n = 4) [ 69 , 72 , 75 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only four studies targeted the lower limbs [ 26 , 61 , 70 , 77 ], all focused on ankle dorsiflexion. The upper limb motor tasks included shoulder ab/adduction (n = 1) [ 63 ], reaching (n = 5) [ 59 , 60 , 65 , 68 , 74 ], grasping (n = 5) [ 4 , 41 , 64 , 66 , 67 ], reaching and grasping (n = 2) [ 71 , 73 ], hand and wrist extension (n = 2) [ 22 , 23 ], and finger extension (n = 4) [ 69 , 72 , 75 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…The number of training sessions varied from 1 to 80 sessions, with six studies below 10 sessions [ 60 , 61 , 68 , 71 , 72 , 77 ], 11 between 10 to 15 sessions [ 22 , 23 , 26 , 41 , 59 , 65 67 , 69 , 70 , 75 ], and six with more than 15 sessions [ 4 , 63 , 64 , 73 , 74 , 76 ]. It is noteworthy that Takahashi et al [ 77 ] and Mrachacz-Kersting et al [ 61 ] demonstrated improvements after only one session of BCI-NFT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BCI is also being used for motor recovery in patients who have suffered from a stroke or other injury which often leaves them with the inability to move. This is done by measuring changes in neuronal activity over the motor cortex during a MI task whilst providing them with a reward in the form of a virtual avatar performing the same movement and/or with a robotic device [4], [5], [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…The BCI Competition IV was especially focused on the oscillatory brain activity associated with different motor tasks such as MI and motor execution (ME) [4]. This is because a major application area of BCI technology is in rehabilitating the motor impairments of neurologically disabled people by promoting neuroplasticity [6], [7]. There were 5 different datasets in this competition across three different brain modalities such as EEG, MEG, and ECoG.…”
Section: Introductionmentioning
confidence: 99%